Chemical Design Model for Emergent Synthetic Catch Bonds - van Galen, Martijn; van der Gucht, Jasper; Sprakel, Joris (Frontiers in Physics, 2020)
All primary chemical bonds inherently weaken under increasing tension. Interestingly, nature is able to combine such bonds into protein complexes that accomplish the opposite behavior: they strengthen with increasing tensional force. These complexes known as catch bonds are increasingly considered a general feature in biological systems subjected to mechanical stress. Despite their prevalence in nature however, no truly synthetic realisations of catch bonds have been accomplished so far, as it is a profound challenge to synthetically mimic the allosteric mechanisms employed by protein catch bonds. In this work we propose a computational model that shows how a synthetic catch bond could be accomplished with the help of existing supramolecular motifs and mechanophores, each of which individually act as slip bonds. This model allows us to identify the limits of catch bonding in terms of a number of experimentally measurable parameters. This knowledge could be used to suggest potential molecular canditates, thereby providing a foothold in the ongoing pursuit to realize synthetic catch bonds.